Rwanda's Exit Pathway from Violence : A Strategic Assessment - Shahabudin McDoom, Omar (World Bank, Washington, DC, 2017)
This report aims to assess the steps taken during Rwanda's transition following the genocide against the objective of the long-term durability of domestic peace. Its principal conclusion is that peace is most likely to endure if Rwanda's political space is gradually opened up to allow: (i) Rwanda's formal state institutions to establish greater autonomy from the current regime; and (ii) Rwandan political and civil society, its political opposition and media in particular, to evolve as mature and independent counterweights to the ruling party. Incremental political liberalization will encourage an important shift in Rwanda's political culture to one which encouraged accountability for the subordination of institutional rules to personal, party, or ethnic interests. It falls on the regime to show the way forward to Rwanda's civil and political society by demonstrating its tolerance for genuine political pluralism, dissent, and inclusion. It is in the regime's long-term strategic self-interest to encourage such a change in political culture and increase its legitimacy in order to discourage attempts to bring about regime change extra-constitutionally.